Position paper on early childhood mathematics (Edma 0-6: Educación Matemática en la Infancia, 2012)
This is a joint position paper of the Australian Association of Mathematics Teachers and Early Childhood Australia on Early Childhood Mathematics.
Keywords: Early Childhood Education; Mathematics Education; The Australian Association of Mathematics Teachers; Early Childhood Australia